ULTRASTRUCTURE OF MESENTERON OF PANTALA FLAVESCENS FABR. (LIBELLULIDAE : ODONATA) - BHARDWAJ, A.C.; TIYAGI, NEELAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
Scanning electron microscopic study of Pflavescens Fabr, mesenteron has revealed longitudinal folded inner surface, with numerous irregularly disposed villose. These villose have been considered as an assemblage of secretory cells. The nidi have situated at the base of each fold; slipping out slightly and accomodated well within the musculature. The external surface of mesenteron possesses longitudinal, circular muscle bundles and profuge vascular and tracheal supply. The distinct oesophageal valve incorporates zones of muscle reversal and epithelia deflection. The peritrophic membrane has been poorly sighted at this place, however the same has been noticed distinct in rest of the mesenteron. The pyloric valve made up of six to eight pyloric pads. The significance of valves, rich blood and aerial supply in the mesenteron have been discussed.